Concept of Ar-Rahnu and its application at Bank Rakyat Saujana Utama / Siti Hanis Rosli - Rosli, Siti Hanis (Academy of Contemporary Islamic Studies (ACIS), 2016)
This study was conducted to determine the concepts and applications ar-Rahnu of Bank Rakyat at Saujana Utama. This study refers to the sources of true and authoritative of Al-Quran and Al-Sunnah and the opinion of the scholars in explaining the concept of arRahnu. This research focuses on Islamic pawn scheme named as ar-Rahnu that was offered in the Bank Rakyat at Saujana Utama. Ar-Rahnu implementation of the scheme is so committed to the bank, hence making it as one of banking products offered at all branches. The study also deals with how to unlock the application of ar-Rahnu in Bank Rakyat and also the difference between ar-Rahnu scheme and conventional pawn broking.